Phytochemical and network-based chemotaxonomic study on Thalictrum foliolosum. (October 2022) - He, Gongxiu; Tu, Xichen; Yan, Yuanfeng; Peng, Jun; Yin, Tianpeng
Abstract: Phytochemical investigation on the whole herbs of Thalictrum foliolosum DC. (Ranunculaceae) led to the isolation of eighteen compounds, including nine isoquinoline alkaloids (1 –9 ) and nine nonalkaloidal constituents (10 –18 ). Among them, compounds 11 –14 and 16 –18 have not been previously isolated from this genus, while compounds 1, 7, 10, and 15 have not been previously found in this species. The chemotaxonomic values of these compounds were explored by compound-species network analysis. Some of the isolated compounds (1, 7, 10 ) showed limited distribution in the genus, which could serve as chemotaxonomic markers to facilitate species identification of T. foliolosum . Highlights: Nine isoquinoline alkaloids and nine nonalkaloidal constituents were isolated from Thalictrum foliolosum. Seven compounds have not been previously isolated from this genus. Nonalkaloidal constituents were isolated from T. foliolosum for the first time.